Workshop Pengurangan Risiko Bencana untuk Civitas Akademika MIM Terpadu Harapan Kota Magelang - Kanthi Pamungkas Sari; Margono; M. Tohirin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Madrasah is considered effective in implementing Disaster Risk Reduction (DRR) education, from disseminating disaster knowledge to action. However, some of the academic community of MIM Terpadu Harapan Magelang City understand that DRR is essential; until now, it has never been a priority for the Madrasah program. This community service activity aims to increase the capacity of human resources in preparedness to face multihazard disasters. Method: The activity partners are the Academic Community of MIM Terpadu Harapan Magelang City and 27 participants who participated in the workshop. The procedures carried out in community service include three stages: the preparation stage, the activity stage, and the activity evaluation stage. Results: Participants' responses during the workshop were excellent; participants carried out actively and enthusiastically from start to finish. Participants can compile disaster risk assessments according to the objective conditions of the surrounding environment. Participants quickly assembled the MIM Integrated Disaster Preparedness Task Force Harapan Magelang City along with its work description in the follow-up plan. Conclusion: Community service activities can increase human resources' capacity to prepare for multi-hazard disasters.